Examining the Hepatic Immune System in Children With Liver Disease With Fine Needle Aspiration. Issue 2 (February 2022) - Yuksel, Muhammed; Demirbaş, Burak; Mizikoğlu, Özlem; Tütüncü, Yildiz; Kanmaz, Turan; Oğuzkurt, Levent; Arikan, Cigdem
ABSTRACT: Objectives: Liver biopsy is the standard in diagnosing liver diseases. Yet, it provides little space to perform comprehensive immune profiling of the liver. Hence, we explored whether fine needle aspirates (FNAs) could be used to elucidate the hepatic immunity in children. Methods: We enrolled 74 children undergoing diagnostic (n = 17) or protocol biopsy (n = 57) following liver transplantation (LT). Matched blood and FNAs were obtained. Additionally, explant liver tissue was collected from children (n = 14) undergoing LT. Immune cells were isolated from peripheral blood, FNAs and explanted livers. Immune-phenotypical profiling was done by flow cytometry. Results: Biopsied patients (58% female) were at a median age of 46 months (interquartile range [IQR]: 12–118) and LT patients (71% female) were 48 months (IQR: 21–134, P = 0.78) old. CD69 +, a hallmark of tissue-resident immune cells was expressed in 1.3% of CD3 + T cells from blood being higher in FNA (20%) and tissue (49%, P < 0.001). CD4 + T-cell frequencies in tissue (13%) and FNAs (20%) were lower compared to blood (35%, P < 0.001) whereas CD8 + T cells in tissue (33.5%) and FNA (32%) were higher than in blood (25%, P < 0.01). Mucosal associated invariant T cells were enriched in liver tissue (8.8%) and in the FNA (4.4%) compared to blood (1.7%, P < 0.001). Whereas the percentage of total Tregs (CD4 + CD25 + FOXP3 + CD127 low/− ) decreased, the proportion of activated Tregs (CD4 + CD45RA-FOXP3 high ) increased in FNA and explant. Breg (CD19 + CD20 + CD24 high CD38 high ) frequencies were similar in all groups. Conclusion: FNA is a practical method to sample the liver immune system collecting even small cell subsets such as regulatory T/B cells. Abstract : Supplemental Digital Content is available in the text